Lorcaserin maintenance fails to attenuate heroin vs. food choice in rhesus monkeys. (1st March 2020) - Townsend, E. Andrew; Negus, S. Stevens; Poklis, Justin L.; Banks, Matthew L.
Graphical abstract: Highlights: Saline substitution reduced responding on heroin choice and increased food choice. Naltrexone maintenance decreased heroin choice and increased food choice. Lorcaserin maintenance increased heroin-vs-food choice. Abstract: Background: The current opioid crisis has reinvigorated preclinical research in the evaluation of non-opioid candidate treatments for opioid use disorder (OUD). Emerging evidence suggests 5-HT2C receptor agonists may attenuate the abuse-related effects of opioids. This study evaluated effectiveness of 7-day treatment with the clinically available 5-HT2C agonist lorcaserin (Belviq®) on heroin-vs.-food choice in rhesus monkeys. Lorcaserin effects were compared to effects produced by 7-day saline substitution and by 7-day treatment with the opioid antagonist naltrexone. Methods: Adult male (1) and female (6) rhesus monkeys were trained to respond under a concurrent schedule of food delivery (1 g pellets, fixed-ratio 100 schedule) and intravenous heroin injections (0-0.032 mg/kg/injection, fixed-ratio 10 schedule) during daily 2 h sessions. Heroin choice dose-effect functions were determined daily before and following 7-day saline substitution or 7-day continuous treatment with naltrexone (0.0032-0.032 mg/kg/h, IV) or lorcaserin (0.032-0.32 mg/kg/h, IV). Results: Under baseline conditions, increasing heroin doses maintained a dose-dependent increase in heroin choice. Both saline substitution and 7-day naltrexone treatment significantly attenuated heroin choice and produced a reciprocal increase in food choice. Continuous lorcaserin (0.32 mg/kg/h) treatment significantly increased heroin choice. Conclusions: In contrast to saline substitution and naltrexone, lorcaserin treatment was ineffective to reduce heroin-vs.-food choice. These preclinical results do not support the therapeutic potential and continued evaluation of lorcaserin as a candidate OUD treatment.